DETERMINATION OF VENTRICULAR LATE POTENTIALS IN PERSONS WITH HIGH NORMAL BLOOD PRESSURE - Isayev, I.I.; Rasul, I.T.; Fataliyeva, M.M.; Rzayeva, R.A.; Gahramanova, D.I. (World of Medicine and Biology, 2025)
Disturbances in the autonomic regulation of the heart are the earliest predictors of complications such as arrhythmia and sudden cardiac death against the background of high normal blood pressure. With the purpose to study the signs of myocardial electrical instability, we registered indicators of high-resolution electrocardiography. According to our results, a statistically significant difference was observed in group with high normal blood pressure for RMS40 and for the TotQRSf/RMS40 index as p